Impact of the Ultrasound-Guided Serratus Anterior Plane Block on Post-Mastectomy Pain: A Randomised Clinical Study - Rahimzadeh, Poupak (Turk J Anaesthesiol Reanim, 2018)
OBJECTIVE: A variety of methods, including neuraxial and regional blocks, have been used to manage post-mastectomy pain. This study evaluates the effect of serratus anterior plane block on acute pain after mastectomy. METHODS: A total of 60 patients who were candidates for mastectomy under general anaesthesia were divided in this trial into two groups. After entering the recovery room, the first-experimental-group (SAB) underwent the ultrasound-guided serratus anterior block, but the second-control-group (CTL) received no block intervention. An intravenous patient-controlled analgesia (PCA) device was used to deliver fentanyl in both groups. Using the Visual Analog Scale (VAS), the patients’ pain was assessed at intervals of 1, 6, 12 and 24 hours after entering the recovery room. Intravenous acetaminophen was administered as a rescue analgesic if the pain exceeded 3 on the VAS. A total amount of fentanyl consumed, the time to first PCA request, a total amount of acetaminophen consumption and possible adverse effects were evaluated. RESULTS: The pain scores assessed at the time intervals were not significantly different between the two groups (p>0.5). The total consumption of fentanyl was significantly lower in the SAB group than in the CTL group (p=0.0001). Duration of the time to first PCA request was remarkably longer in the SAB group than in the CTL group (p=0.0001). The total amount of acetaminophen consumed was notably higher in the CTL group than in the SAB group (p=0.001). None of the patients experienced side effects. CONCLUSION: Undertaking serratus anterior block following mastectomy can reduce pain scores and lower opioid usage.